2016
DOI: 10.15740/has/tajh/11.2/329-334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cherry tomato [Solanum lycopersicum L. var. cerasiforme (Dunnal) A. Gray] genotypes for yield and quality traits

Abstract: The present research work was undertaken to identify the genetically divergent genotypes for higher yield and desirable quality traits under shade net in tropical climatic condition. The study consisted of eighteen genotypes collected from different places were raised, evaluated and studied for mean performance for yield and yield contributing traits and for quality traits. Based on per se performance of genotypes, the genotype Solan Red Round was adjusted as the best for tropical condition, since it had recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
7
10
0
2
Order By: Relevance
“…The lowest yield hectare -1 of 12.25 tonnes was noted in IIHR 2876. These results were in agreement with the reports of Renuka et al, (2014) and Ramya et al, (2016) in cherry tomato.…”
Section: Yield Contributing Characterssupporting
confidence: 94%
See 4 more Smart Citations
“…The lowest yield hectare -1 of 12.25 tonnes was noted in IIHR 2876. These results were in agreement with the reports of Renuka et al, (2014) and Ramya et al, (2016) in cherry tomato.…”
Section: Yield Contributing Characterssupporting
confidence: 94%
“…Indu Rani (2002) also concluded that the parents exhibited higher per se for fruit weight in tomato. It also conformity with the findings of Macua et al, (2009), Boches et al, (2011 and Ramya et al, (2016) in cherry tomato.…”
Section: Yield Contributing Characterssupporting
confidence: 93%
See 3 more Smart Citations